Strategic Agility in Pesantren; Navigating Educational Change through Adaptive Institutional Practices - Gheitzaa Zahiraa Shoofia; Rahimah Embong; Fathor Rozi (Universitas Nurul Jadid, 2025)
This study aims to analyze the implementation of agility strategies at Al-Mashduqiyyah Islamic Boarding School, Patokan Probolinggo, in responding to change and the demands of modern education. The study focuses on curriculum management, the role of pesantren caregivers (kyai), and pesantren culture as the foundation of institutional resilience. This research adopts a qualitative approach with a case study design, in which data were collected through in-depth interviews, observations, and documentation. The selection of informants was conducted purposively to ensure the richness and relevance of the data obtained from key stakeholders within the pesantren environment. The findings indicate that agility strategies at Al-Mashduqiyyah are realized through flexible and contextual curriculum management by integrating the religious curriculum based on kitab kuning with the national formal curriculum. This integration enables students to achieve a balanced competence between religious mastery and general academic skills. The pesantren caregivers play a central role in promoting organizational agility through monitoring changes, making adaptive decisions, and delegating authority to administrators and educators in a structured yet dynamic manner. Moreover, the pesantren culture, which upholds the values of deliberation (musyawarah), discipline, sincerity, and respect for tradition, functions as a key pillar in maintaining a balance between innovation and the preservation of pesantren values. These cultural values strengthen institutional identity while simultaneously encouraging responsiveness to external challenges. Therefore, the agility strategy implemented at Al-Mashduqiyyah Islamic Boarding School is not only an adaptive response to change but also a sustainability strategy rooted in the values and culture of the pesantren, ensuring its long-term relevance and institutional continuity in the modern educational landscape